RNA-seq analysis of shrimp tropomyosin-induced allergic reactions through PI3K/Akt pathway - Li, Yanchu; Yang, Yuying; Li, Junyao; Guo, Rui; Niu, Zhiqiang; Hu, Weicheng; Liu, Shucheng; Wei, Shuai (Frontiers in Nutrition, 2025)
IntroductionTropomyosin (TM) is the primary allergen in Litopenaeus vannamei, which usually causes allergic reactions that may be health or even life-threatening for consumers. Therefore, exploring the sensitization mechanism is of great significance for the prevention and treatment of tropomyosin allergy.Methods and resultsIn this study, TM sensitization models were using Balb/c mice, Caco-2 cells and RBL-2H3 cells to reveal the sensitization effect. The results of ELISA and RT-qPCR showed that TM can exacerbate the allergic reaction by reducing the mRNA expression of tight junction (TJ) proteins (such as ZO-1, claudin-3, Occludin) in the jejunum, destroying the intestinal barrier function, increasing the permeability, and promoting the release of inflammatory factors (such as IL-8, TNF-α) and histamine. The pathological results of intestinal tissue sections showed that TM also caused an increase in intestinal inflammatory infiltration in mice. RNA-seq analysis revealed that key genes (CCL2, HSP1A, GM-CSF, etc.) and PI3K/Akt signaling pathway were involved in the sensitization process. In vitro experiments were conducted to construct TM sensitized Caco-2 and RBL-2H3 cell models at a dose of 100 mg/mL. The results indicated that TM upregulated the expression of phosphorylated PI3K/ Akt and NFκB pathways in Caco-2 cells, further damaged the TJ structure of intestinal epithelial cells and promoted the release of inflammatory factors. The RBL-2H3 cell degranulation assay indicated that TM could directly stimulate the release of TNF-α from mast cells.ConclusionThe above experimental results indicated that PI3K/Akt signaling pathways play a crucial role in the induction of TM allergic responses, which provides a theoretical basis for the occurrence, development and prevention of TM allergy.